Les connectivites : prévalence, profils clinique, thérapeutique et évolutif dans le service de médecine interne de l’établissement public hospitalier de Laghouat - ABIZIANE HALIMA; Encadreur : Dr F. BENMEDIOUNI (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
The Connective Tissue Diseases (CTD) are a group of conditions that have in common a diffuse, inflammatory and chronic damage of connective tissue. They are increasingly diagnosed in Algeria. The aim of this study was to define the prevalence as well as the clinical, therapeutic and evolutionary profile of CTD in the internal medicine department in Laghouat hospital in order to initiate research perspectives in this area. Material and methods This is a retrospective, descriptive, observational study, on patient files, including 25 patients who presented CTD, and who were hospitalized in the internal medicine department of LAGHOUAT hospial, over a period of 28 months (from September 2018 until December 2020 included).
250 p.